2014
DOI: 10.4014/jmb.1309.09001
|View full text |Cite
|
Sign up to set email alerts
|

454 Pyrosequencing Analysis of Bacterial Diversity Revealed by a Comparative Study of Soils from Mining Subsidence and Reclamation Areas

Abstract: Significant alteration in the microbial community can occur across reclamation areas suffering subsidence from mining. A reclamation site undergoing fertilization practices and an adjacent coal-excavated subsidence site (sites A and B, respectively) were examined to characterize the bacterial diversity using 454 high-throughput 16S rDNA sequencing. The dominant taxonomic groups in both the sites were Proteobacteria, Acidobacteria, Bacteroidetes, Betaproteobacteria, Actinobacteria, Gammaproteobacteria, Alphapro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 57 publications
8
32
1
Order By: Relevance
“…Rhizobium present in all soil samples is a major contributor to the global nitrogen cycle as it forms a symbiotic nitrogen fixation with many plants. It also improves soils fertility, promotes circulation of soil materials and increases soil microbial activity [31]. The relative abundance of Buckholderia observed in the unlimed soil is consistent with the recent classification of this genus as an acid tolerant group [45].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Rhizobium present in all soil samples is a major contributor to the global nitrogen cycle as it forms a symbiotic nitrogen fixation with many plants. It also improves soils fertility, promotes circulation of soil materials and increases soil microbial activity [31]. The relative abundance of Buckholderia observed in the unlimed soil is consistent with the recent classification of this genus as an acid tolerant group [45].…”
Section: Discussionsupporting
confidence: 78%
“…Pyrosequencing has been used to analyze bacteria population dynamics [3133]. In the present study, analysis of two types of soil samples showed a higher relative abundance of bacterial species and genera compared to fungi.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Next, the mining intensity has a direct relationship with the mining subsidence, thus changing the physical and chemical properties of soil and further interfering with the soil bacterial communities [7,10,38,96,104]. The effects of several other possible factors on the soil bacterial communities were not negligible, and these effects are still under investigation.…”
Section: Uncertainties Of Soil Bacterial Development In Ecological Prmentioning
confidence: 99%
“…The Datong (DT) coal-mining area (39 • 53 24"N-40 • 10 00"N, 112 • 52 13"E-113 • 32 35"E) is also located in Shanxi Province, China (Figure 1). This area used as the representative semiarid area in Northern-Western China, has a continental climate and a mean annual Microorganisms 2020, 8,433 4 of 22 temperature of 6.4 • C. The mean annual precipitation is 384.6 mm, with precipitation mainly occurring from June to September. The collected soil type is loess and from the damaged mining areas.…”
Section: Study Sites Soil Sampling and Measurmentmentioning
confidence: 99%